Analisis Kebutuhan Diklat Widyaiswara dalam Metode Pembelajaran Blended Learning Di PT. X - Ningrum, Reka Sulistya; Ahmad, Fandi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2023)
Employee competence is crucial in the success or failure of an organization in responding to environmental changes, as happened at PT. X, where this company seemed not ready to welcome post-pandemic conditions, this is known from the presence of employees who are considered incompetent. The purpose of this study is to conduct an analysis related to the readiness of widyaiswara competencies at PT. X in facing the learning transition based on blended learning and conducting AKD (Training Needs Analysis) related to training that can support the readiness of widyaiswara competencies at PT. X in dealing with blended learning based learning. This research method is descriptive - quantitative because the process of collecting, searching and obtaining data serves to describe real or actual conditions in the field with the help of instruments in the form of questionnaires. Based on the analysis, it was found that the competence readiness of the widyaiswara as a facilitator was capable in the very incapable category with a score of 3%, the category unable to get a score of 11%, the sufficient category to get a score of 14%, the able category to get a score of 49%, and the very able category to get a score 23%. The interpretation of the bar chart found that 7 people needed training in designing proposed learning materials in blended learning, 13 people needed training in designing thinking design training, 9 people needed training in creating learning content, 12 people needed assessment training in blended learning and 10 people needed training to become facilitators professional blended learning. departing from this phenomenon, PT.X must immediately optimize the training needs analysis process so that it can encourage the organization to move more dynamically in facing future challenges.